Harmony: a new way of looking at our world - Charles, III., Großbritannien, König (HarperCollins, 2010)
In this informational, inspirational work, Charles, the Prince of Wales, describes his views on climate change for the first time, presenting a compelling case that the solution to this problem lies in our ability to regain our balance with nature